2008
DOI: 10.1177/0961203308089436
|View full text |Cite
|
Sign up to set email alerts
|

Childhood agricultural and adult occupational exposures to organic dusts in a population-based case–control study of systemic lupus erythematosus

Abstract: Organic dust exposure can influence the development and symptoms of immune-related diseases such as atopy and asthma, but has rarely been examined in relation to systemic autoimmunity. The present analyses explore the association of lifetime farm and occupational organic dust exposures with systemic lupus erythematosus (SLE) in recently diagnosed patients (n = 265) compared with controls (n = 355) frequency matched by age, sex and state. Questionnaire data included childhood farm residence, childhood and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…This may reflect a true predominance of SLE and SSc among First Nations females, and is consistent with previous studies of SARD in First Nations populations, which also reported a genetic predisposition to autoimmune disorders and more severe disease phenotypes (7)(8)(9)(10)(11). It is interesting, however, to hypothesize that this increased prevalence is a result of environmental exposures in a population predisposed to SARD, since, for example, silica exposure has been suggested as an environmental trigger for SARD (30,31). Although a protective factor conferring improved survival could also increase prevalence estimates, this seems less likely given the more severe disease phenotypes and difficulties accessing health care reported in First Nations populations.…”
Section: Discussionsupporting
confidence: 75%
“…This may reflect a true predominance of SLE and SSc among First Nations females, and is consistent with previous studies of SARD in First Nations populations, which also reported a genetic predisposition to autoimmune disorders and more severe disease phenotypes (7)(8)(9)(10)(11). It is interesting, however, to hypothesize that this increased prevalence is a result of environmental exposures in a population predisposed to SARD, since, for example, silica exposure has been suggested as an environmental trigger for SARD (30,31). Although a protective factor conferring improved survival could also increase prevalence estimates, this seems less likely given the more severe disease phenotypes and difficulties accessing health care reported in First Nations populations.…”
Section: Discussionsupporting
confidence: 75%
“…In this same sample, there was no association of SLE with application of pesticides, an activity presumed to involve lower exposures than mixing (2). However these analyses did not adjust for other agricultural exposures (other than silica), including organic dust (livestock/grain dust) exposure (1), which was later identified as potentially protective factor. Another case-control study conducted through rheumatology centers across Canada did not find any association with occupational pesticide use (4).…”
Section: Exposuresmentioning
confidence: 99%
“…Increased SLE mortality was observed in long-term follow-up of a Taiwanese population accidentally exposed to high levels of PCBs and furans through consumption of contaminated rice, with SLE deaths starting 10 years after the exposure (39). Development of a lupus-like syndrome has been observed in two different strains of mice (C57BL/6 and SNF (1)) following mid-gestation dosage with TCDD, with some differences in effect by sex (40, 41). In contrast, a study of New Zealand Black/New Zealand White F1 hybrid (B/W) mice injected with TCDD since 6 weeks of age found exposure to be suppressive of SLE disease activity (32).…”
Section: Exposuresmentioning
confidence: 99%
See 2 more Smart Citations